Axisymmetric squeezing of a Phan‐Thien and Tanner lubricant film under imposed constant load in the presence of a poroelastic medium. (7th May 2015) - Yousfi, Mahdia; Bou‐Saïd, Benyebka; Tichy, John
Abstract: In this paper, a modified Reynolds equation in polar coordinates using the Phan‐Thien and Tanner rheological model is combined with a modified Darcy law describing a poroelastic confining surface. The Phan‐Thien and Tanner model is commonly used to describe the viscoelastic behaviour of synovial fluid, while the poroelastic model can portray articular cartilage. Together, they may provide a simulation basis for lubrication of the tribology of the knee contact under squeezing. The results obtained for the axisymmetric case are analysed and compared for certain non‐Newtonian shear phenomena on the basis of works from the literature. Copyright © 2015 John Wiley & Sons, Ltd.